Monte Carlo Modeling of Computed Tomography Ceiling Scatter for Shielding Calculations. Issue 4 (April 2016) - Edwards, Stephen; Schick, Daniel
Abstract : Abstract: Radiation protection for clinical staff and members of the public is of paramount importance, particularly in occupied areas adjacent to computed tomography scanner suites. Increased patient workloads and the adoption of multi-slice scanning systems may make unshielded secondary scatter from ceiling surfaces a significant contributor to dose. The present paper expands upon an existing analytical model for calculating ceiling scatter accounting for variable room geometries and provides calibration data for a range of clinical beam qualities. The practical effect of gantry, false ceiling, and wall attenuation in limiting ceiling scatter is also explored and incorporated into the model. Monte Carlo simulations were used to calibrate the model for scatter from both concrete and lead surfaces. Gantry attenuation experimental data showed an effective blocking of scatter directed toward the ceiling at angles up to 20–30° from the vertical for the scanners examined. The contribution of ceiling scatter from computed tomography operation to the effective dose of individuals in areas surrounding the scanner suite could be significant and therefore should be considered in shielding design according to the proposed analytical model.